Analisis Sekolah sebagai Sistem Sosial dalam Meningkatkan Interaksi Sosial Guru dan Murid - Naila, Syafiatu; Pratama, Andi Riswan; Yasin, Muhammad (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2024)
The purpose of this research is to find out the meaning of school as a social system and the factors that influence social interaction in schools by using qualitative methods and descriptive approaches. Qualitative research methods collect data in the form of descriptions and illustrations. The research location is at SMPIT Daarussalaam Sangatta Utara. The results showed that students who participated in the organization had a more social spirit than students who didn’t participate in the organization. Because several factors influence this. The impact of students who don’t participate in the organization is a low social spirit, sense of empathy, and lack of leadership. The solution is that every man and woman must understand differences, think wisely, and be able to develop their potential. This research confirms that in this modern era, generations must have a good social spirit and have great potential to shape a more advanced world. Therefore, educational institutions need to provide support and resources to help young people build their social spirit.